What Really Changed? Environments, Instruction, and 21st Century Tools in Emergency Online English Language Arts Teaching in United States Schools During the First Pandemic Response - Turchi, Laura B.; Bondar, Natalia A.; Aguilar, Leonard L. (Frontiers in Education, 2020)
In this article, a teacher educator and two veteran teachers of 9–12 English Language Arts (ELA) inquire into the opportunities, challenges, and lessons learned from the abrupt transition to online learning caused by the COVID-19 pandemic. The shared setting was a major metropolitan area. The fundamental question addressed is What really changed? In ELA classes that were already rich in digital resources, and where assignments were regularly submitted using internet-based learning management systems, the Spring 2020 school close-down and move to online instruction nevertheless meant profound changes to the authors’ teaching lives. In this article they investigate the approximately 12 weeks that concluded the first pandemic semester, focusing on the impact on teaching and learning environments, instructional purposes, and 21st century tools. The authors believe these changes will have consequences in future classrooms, in whatever physical or virtual contexts teachers find themselves delivering instruction.